Daya Tarik Nama Prodi Dan Gelar Pada Minat Siswa Kelas Xii Kuliah Di Perguruan Tinggi - Faozen2; Manggala, Adhitya Surya (Universitas Muhammadiyah Jember, 2023)
The increasing number of educational institutions in Indonesia makes its managers have to think hard in developing it. These managers need to make strategies so that their educational institutions can win the competition in the market. In addition, education managers also need to understand the interests and desires of prospective students. To find out how high the interest of students to go to college, research was conducted using the comparative causal method. The results showed that out of 1,120 respondents, as many as 84.6% or 948 students wanted to go to college, while 15.4% or 172 students did not want to go to college. Of the students who want to study, as many as 63.8% or 715 students are interested in studying in applied tourism graduates. The remaining 36.2% or 405 students did not want to study in tourism science. In the category of applied tourism undergraduates, as many as 16.3% or 182 students want to study tourism science, while 43.6% or 448 students want to study tourism business management. In addition, as many as 16.2% or 181 students want to study hospitality management, 13.8% or 155 students want to study in travel business management, and the rest, 10.2% or 114 students want to study in gastronomy. From the results of this study, it can be concluded that applied tourism graduates are the most popular choice for prospective students